A Prospective Study Evaluating the Etiologic Spectrum in Patients with Dysphagia in Coastal Odisha Using Clinical Features and Endoscopy - Panigrahi, Subhendu; Khatua, Chitta Ranjan; Mishra, Debakanta; Parida, Prasanta Kumar; Singh, Shivaram Prasad (Journal of Digestive Endoscopy, 2019)
Background: There is scarcity of data on the etiological spectrum of dysphagia from India. The study was conducted to determine the etiological spectrum of dysphagia in coastal Odisha.Materials and Methods: Consecutive patients presenting with dysphagia to the gastroenterology outpatient department in 2017 were studied. Patients were evaluated with meticulous history, clinical examination, esophagogastroduodenoscopy, and chest X-ray. Barium study and endoscopic biopsy were done when necessary.Results: Of 216 consecutive patients, 122 (56.48%) were male and 94 (43.52%) were female with a mean age of 42.3 ± 17.4 years. The common etiologies were benign stricture in 68 (31.48%) and esophageal carcinoma in 51 (23.62%). Other etiologies included achalasia cardia in 11 (5.09%), esophageal candidiasis in 10 (4.63%), pharyngeal cancer in 4 (1.85%), and esophageal web in 3 (1.39%). In 63 (29.17%) cases, no etiology was detected. Most of the benign strictures were due to corrosive injury in 48 (70.59%); other causes included peptic stricture (8, 11.76%), postsurgery (4, 5.88%), sclerotherapy-induced stricture (2, 2.94%), and pill-induced stricture (2, 2.94%); in 4 (5.88%) cases, the cause of stricture was not known. The most common cause of corrosive injury was acid injury in 38 (79.17%), followed by alkali injury in 4 (8.34%). In 6 (12.5%) cases, the nature of corrosive was not known. Most of the corrosive injuries were due to suicidal intake.Conclusion: In this study, the most common cause of dysphagia was benign corrosive stricture due to suicidal intake of corrosives. Esophageal carcinoma, achalasia cardia, and esophageal candidiasis were other significant etiologies. Uncommon causes of dysphagia included esophageal web, pharyngeal cancer, and reflux esophagitis.
Keywords: barium study; benign stricture; corrosive injury; esophagogastroduodenoscopy